Gait Analysis: The Effect of Suspension Type in Transfemoral Patient - Rahmawati, Linda; Hjelmstrom, Olle; Widada, Ns.; Mughnie, Burlian (Journal of Prosthetics Orthotics and Science Technology, 2022)
Background: common problems that occur in patients with transfemoral is the lack of stability during using the prosthesis and will result in gait deviation. One of the most important components in improving the stability of the patient is the selection of the type of suspension that appropriate to the patient's needs so as to improve gait. Objective: This study aimed to determine the difference Cadance, walking speed and step length transfemoral patients when using different types of suspension Methods: The study was conducted using the method of observation. Sample research is 4 transfemoral patients have an age of 26-60 years and male sex. Patients were asked to use Silesian belt supesnion and silicone liner with lanyard suspension respectively for 7 days. Observations using tape record. Differences Cadance, walking speed and stride length calculated at the time when patient walks in the 10-meter walking test. Research carried out in clinical laboratories prosthetics and orthotics department. Results: Results indicate that there are significant differences in the type of suspension against Cadance, walking speed and stride length even though significant only on the difference Cadance. Another factor studied in this research is the influence of age and the length of the patient's stump in Cadance, walking speed and stride length. Conclusion: This research found that the Cadance, walking speed and stride length of the transfemoral patients have diffences when using two different types of suspension.